How do demographic transitions and public health policies affect patients with Parkinson’s disease in Brazil? - Bovolenta TM (Dove Medical Press, 2017)
Tânia M Bovolenta, Andre C Felicio R. Neurology Program, Hospital Israelita Albert Einstein, São Paulo, Brazil Abstract: Brazil is currently experiencing a significant demographic transition characterized by a decrease in fertility rates and an exponential increase in the number of elderly citizens, which presents a special challenge for the health care professionals. More than other portions of the population, the elderly are most commonly affected by chronic diseases such as Parkinson’s disease. Policymakers contend that Brazil is reasonably well-prepared regarding elderly health care, with policies that aim to ensure the quality of life and the well-being of this portion of the population. However, what happens in practice falls short of what the Brazilian Constitution sets forth. Specifically, there is a clear contradiction between what the law recognizes as being a citizen’s rights and the implementation of guidelines. Because health financing in Brazil remains relatively low, the civil society tries to fill in the gaps as much as possible in the treatment of elderly patients suffering from chronic diseases such as Parkinson’s disease. In this review, we outline the current legislation in Brazil regarding the elderly and in particular, patients with Parkinson’s disease, in the context of a rapidly aging population. Keywords: Parkinson’s disease, demographic transition, public health, health assistance financing